Energy and exergy analysis of a supercritical water gasification system for the simultaneous production of hydrogen, heat, and electricity from sugarcane bagasse - Bimestre, Thiago Averaldo [UNESP]; Castro, Thais Santos [UNESP]; Rey, José Ramon Copa; Reis e Silva, Valter Bruno; Silveira, José Luz [UNESP] (Elsevier, 2025)
The search for sustainable energy sources and the use of agricultural waste have contributed to an increase in bioenergy research. Promising alternatives include supercritical water gasification (SCWG), which can be used to convert biomass into a hydrogen-rich synthesis gas, along with other value-added products such as bio-oil and process heat. In this context, sugarcane bagasse (SCB), an abundant by-product of the Brazilian sugar-alcohol industry, emerges as a strategic feedstock due to its wide availability and economic potential. This study focuses on hydrogen production by SCWG of SCB and evaluates the cogeneration of electricity, heat, and bio-oil as a secondary by-product by modeling a plant in DWSim. Key parameters such as temperature, biomass concentration, and residence time were evaluated to determine the hydrogen yield of the system as well as its energy and exergy efficiency. In the optimal scenario (700 °C, 25 MPa, 15 wt% biomass), the process achieved a hydrogen production rate of 8.86 mol/kg, generating 38 kW of electricity, 145 kW of heat, and 41 wt% of bio-oil. Overall, this scenario resulted in an energy efficiency of 61.45% and an exergy efficiency of 52.80%, with an eco-efficiency of 394 g CO₂-eq/kWh. The largest energy losses (79.80%) occurred in the supercritical water reactor, in the heat exchangers, and in the combustion chamber, which underlines the need for further optimization of the design. The results confirm the potential of SCWG as a viable pathway for hydrogen production and advanced energy conversion from residual biomass, which is essential for highly efficient and low-carbon utilization of these resources.
Keywords: Bioenergy; Biomass; Gasification; Supercritical water; Thermodynamic analysis